Sosialisasi Pengolahan Limbah Tahu menjadi Energi Alternatif di Industri Tahu Serasi Bandungan - Ery Fatarina P; Retno Ambarwati SL; Teodora Da Silva; Eko Nursanty; Muhammad Fahd Diyar Husni (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
Socialization activities for processing tofu waste into alternative energy were carried out at the Serasi Tofu Industry, Bandungan. This activity aims to provide understanding and skills to tofu entrepreneurs and the surrounding community regarding managing tofu waste into a more environmentally friendly energy source. This outreach includes an introduction to waste processing techniques, such as anaerobic fermentation to produce biogas, and solid residue as organic fertilizer. Through this activity, participants can apply this waste processing technology, thereby reducing the negative impact of tofu waste on the environment and at the same time providing a sustainable energy alternative. The results of the socialization show an increase in awareness and readiness of tofu entrepreneurs to adopt the waste processing methods that have been presented.